(untitled) (Research, Society and Development, 2022)
Introduction: Nurses play a prominent role in welcoming and classifying risk in hospital services. Objective: To understand the role of nurses in welcoming and in risk classification in the hospital service. Methodology: The research was conducted through an integrative review, in which the secondary databases LILACS, SCIELO and BDENF were used, using the descriptors “reception; emergency nursing; emergency medical services and emergency hospital service”. Results: 6 articles on the subject were identified according to the inclusion criteria. Conclusion: Given the above, it was possible to observe a scarce production of articles on the subject. Despite this, it was evident that most articles addressed the relevance of the nurse’s role in the reception in the risk classification, and the need for qualification to provide decisions in a safe way.